Overcoming Transactional Distance through Implementing Podcasts and Vodcasts: Perceptions from an Open Distance and e-Learning University - Kershnee Sevnarayan; Ntshimane Elphas Mohale (International Journal of Pedagogy and Teacher Education, 2022)
The COVID-19 pandemic challenged instructional methods of teaching and learning in universities around the world. To bridge this instructional gap, many universities opted for the use of digital technological innovations to reach students. Despite the implementation of these innovations, many higher education institutions were not fully prepared and ready for online teaching and learning during the pandemic. Researchers have argued that podcast and vodcast implementation in higher education institutions bring about no change to students’ motivation and performance. Consequently, there is still limited research on podcast and vodcast implementation and students’ perceptions on the utilisation of these tools in distance learning contexts. Using email interviews and online open-ended evaluation questions, this article aims to explore first-year undergraduate students’ perceptions of using podcasts and vodcasts to enhance academic writing skills in an open distance and e-Learning university in South Africa. Using transactional distance theory, the findings indicate lecturers and students’ positive perceptions towards the implementation of podcasts and vodcasts because today’s students consume digital content [digital natives], enjoy the use of technology and are adept to navigating online learning. However, even though, at first, novice lecturers were hesitant and unfamiliar with recording podcasts and vodcasts, through mediation, lecturers ended up recording quality podcasts and vodcasts that were clear and made use of illustrations that made it easier for students to understand the module’s content. The researchers recommend that lecturers consider their students’ interests, motivation, language and demographic backgrounds in creating podcasts and vodcasts.